Catch a Wave: The Time Series Behavior of Mergers - Golbe, Devra L.; White, Lawrence J. (The Review of Economics and Statistics, 1993)
This paper offers a direct econometric test of the proposition that U.S. merger activity has occurred in waves. The authors fit a set of sine waves to the annual time-series data on mergers and find that the sine curves generally provide significant explanatory power. The parameters are statistically significant and reasonable in magnitudes, and the implied timing of peaks and troughs in merger activity is close to the actual dates of the peaks and troughs in the data. Thus, this formal test confirms what others have observed impressionistically: the data are consistent with a wave characterization. Copyright 1993 by MIT Press.